The Interpretation of Ecological Preservation in the Awig-awig (Customary Law) Text of Tenganan Pegringsingan Village: Positive Discourse Analysis - I Gede Astawa; Made Budiarsa; Aron Mbete; I Wayan Simpen (e-Journal of Linguistics, 2019)
The earlier research on critical ecolinguistics tended to criticize the negative impacts oflanguage in encouraging ecologically destructive behavior. However, this present study acts differently,it focusses on analysing positive impacts of language in preserving the environment. This present studyaims at analysing the interpretation of ecological preservation revealed in the awig-awig (customarylaw) text belonging to Tenganan Pegringsingan Village. The data of the research were taken fromlexical items, phrases, clauses or sentences used in the written text of the awig-awig. The collected datawere analysed using Positive Discourse Analysis (PDA) developed by Stibbe (2017). The findings ofthe present study showed that the interpretation of ecological preservation in the awig-awig text took theform of preservation of natural ecology, preservation of human ecology, and preservation of spiritualecology. The three findings above correspond to the Tri Hita Karana (THK) concept which wasconsidered the ecosophy (philosophy of ecological harmony) of the study.